Sharp Reductions in Current Account Deficits : An Empirical Analysis - Milesi-Ferretti, Gian (IMF Working Papers; Working Paper ;, 1997)
The paper studies determinants and consequences of sharp reductions in current account imbalances (reversals) in low- and middle-income countries. It poses two questions: what triggers reversals, and what factors explain how costly reversals are? It finds that both domestic variables, such as the current account balance, openness to trade, and the level of reserves, and external variables, such as terms of trade shocks, U.S. real interest rates, and growth in industrial countries, seem to play important roles in explaining reversals in current account imbalances. It also finds some evidence that countries with a less appreciated real exchange rate, higher investment, and more openness before the reversal tend to grow faster after a reversal occurs.